Interplay Between Coastal Elevation and Wave Height Controls the Occurrence of Coastal Boulder Deposits in the Aran Islands, Ireland - Van Blunk, Alexis; Kennedy, Andrew B.; Cox, Rónadh (Frontiers in Earth Science, 2021)
Coastal boulder deposits (CBD) are wave-emplaced supratidal accumulations that record extreme inundation on rocky coasts. They are poorly understood but are of growing importance as we seek to better understand the extremes of wave power on coastlines. The Aran Islands, Ireland, host CBD in varying settings ranging from sheer cliff tops to wide shore platforms, and at elevations to about 40 m above sea level. Deposits are known to be active during strong storm events, and provide a unique opportunity to examine relationships between wave energy, setting, and CBD occurrence. We use topographic elevation (Z) and offshore 100-year significant wave height (Hs,100) to calculate a dimensionless elevation Z*=Z/ Hs,100 at 25m intervals all along the Atlantic-facing coasts of the Aran Islands, and record whether CBD were present or absent at each site. The data reveal universal CBD presence at sites with low dimensionless elevations and near-monotonic decreasing frequency of CBD occurrence as Z* increases. On the Aran Islands, CBD are restricted to sites with Z*<3.13. For high elevation deposits it appears that unresolved local factors may be the major determinants in whether CBD will form. This approach can be applied at any CBD-bearing coastline and has the potential to change the way that we think about these deposits. Implementing the dimensionless elevation at other locations will allow for a broader understanding of the impact local shoreline conditions have on CBD formation. Determining these relationships contributes to the ongoing need to better understand interactions between extreme waves and rocky coasts.